Association between an IL‐28B genetic polymorphism and the efficacy of the response‐guided pegylated interferon therapy in children with chronic hepatic C infection. Issue 4 (13th September 2012) - Komatsu, Haruki; Inui, Ayano; Tsunoda, Tomoyuki; Sogo, Tsuyoshi; Fujisawa, Tomoo
<x xml:space="preserve">Abstract</x> Aim The relation between interleukin‐28B (IL‐28B) genotypes and treatment‐induced hepatitis C virus (HCV) clearance in children is unknown. This was a retrospective study to evaluate the association between an IL‐28B genotype (rs8099917) and pegylated (PEG) interferon (IFN) response. Methods Sixty‐three children (median age, 7 years; range, 3–17 years; 22 with HCV genotype 1 and 41 with genotype non‐1) with chronic HCV infection who were treated with response‐guided PEG IFN on the basis of viral load were evaluated. Results The duration of treatment with PEG IFN was 24 weeks in one child (2%), 36 weeks in eight children (13%), 48 weeks in 36 children (57%), 60 weeks in 11 children (17%) and 72 weeks in seven children (11%). Of the total 63 children, 54 (86%) were initially treated with PEG IFN‐α‐2a monotherapy. The remaining nine (14%) received PEG IFN plus ribavirin as the initial therapy. Of the 54 children initially treated with monotherapy, 35 (65%) continued receiving monotherapy until the end of treatment. In the remaining 19 (35%), monotherapy was changed to PEG IFN plus ribavirin at 12 or 24 weeks of treatment. Of the total 63 children, 54 (86%) achieved a sustained virological response (SVR). In univariate analysis, rs8099917 genotype TT (P = 0.075) showed a weak association with SVR. However, the multivariate analysis revealed no predictive factors which had a significant association with SVR. Conclusion The IL‐28B genotype was not a strong pretreatment predictor for SVR in a mixed genotype cohort of children treated with response‐guided PEG IFN therapy.